From connectors to extension particles, the meaning of sipa ki in Mauritian Creole - Chady, Shimeen-Khan (Taikomoji kalbotyra, 2021)
The extension particles are not considered as discourse markers by all researchers mainly considering the grammatical function the connectors which they are based on can present. However, as for discourse markers which “desemantisation” has been revoked, other researchers argue that extension particles maintain part of their original meaning while endorsing an intersubjective value. I try to study this question in this article for the Mauritian Creole extension particle sipa ki which is formed on the connector sipa. A fine-grained conversational and pragmatics analysis of 6 hours of ordinary conversations, collected in 2014 shows how sipa ki plays a part in conversational relation co-construction. While helping the enunciator to construct their own discourse and showing their attitude towards it, sipa ki provides information on the way the sentence has to be interpreted by soliciting (assumed) shared experience by interlocutors for message reconstruction. I argue that speech effects provided by extension particle sipa ki partly rely on the meaning of connector sipa on which it is constructed and which also holds an intersubjective value.